WEBVTT
00:00:02.760 --> 00:00:11.280
Consider the differential equation two π₯ timesed by dπ¦ by dπ₯ minus two times dπ¦ by dπ₯ equals π¦ squared.
00:00:13.400 --> 00:00:22.080
Part i) In the given figure, sketch a slope field for the given differential equation at the indicated six points.
00:00:24.520 --> 00:00:30.280
Just to clarify, this question has two more parts, which we will answer after we have answered the first part.
00:00:32.520 --> 00:00:37.840
Letβs identify the coordinates of the six points indicated in the figure in part i.
00:00:39.760 --> 00:00:50.080
They are zero, two; zero, one; zero, zero; two, two; two, one; and two, zero.
00:00:52.280 --> 00:01:11.640
To sketch a slope field with the given differential equation at these six coordinates, we must draw short line segments at each of these six coordinators, where the slope of the line segment is equal to the value of dπ¦ by dπ₯ at the coordinate through which the line segment passes.
00:01:12.560 --> 00:01:25.520
To calculate the value of dπ¦ by dπ₯ at each of the six coordinates, letβs rearrange the differential equation to make dπ¦ by dπ₯ the subject.
00:01:25.520 --> 00:01:39.800
Factoring dπ¦ by dπ₯, we obtain that two π₯ minus two multiplied by dπ¦ by dπ₯ equals π¦ squared.
00:01:40.600 --> 00:01:46.200
This means that dπ¦ by dπ₯ equals π¦ squared over two π₯ minus two.
00:01:46.400 --> 00:01:55.440
Substituting the coordinate zero, two into the expression for dπ¦ by dπ₯, we obtain two squared divided by two times zero minus two, which is equal to negative two.
00:01:57.800 --> 00:02:04.200
Similarly, we find that the value of dπ¦ by dπ₯ at the coordinate zero, one is negative a half.
00:02:05.440 --> 00:02:11.200
The value of dπ¦ by dπ₯ at the coordinate zero, zero is zero.
00:02:11.800 --> 00:02:15.680
The value of dπ¦ by dπ₯ at the coordinate two, two is two.
00:02:15.680 --> 00:02:20.720
The value of dπ¦ by dπ₯ at the coordinate two, one is a half.
00:02:20.720 --> 00:02:25.800
And the value of dπ¦ by dπ₯ at the coordinate two, zero is zero.
00:02:26.000 --> 00:02:35.880
Now that we have found the slopes of the line segments at each of the six coordinates, letβs draw the line segments on the figure provided.
00:02:36.680 --> 00:02:38.160
Letβs start with the coordinates zero, zero and two, zero.
00:02:40.040 --> 00:02:49.160
The value of dπ¦ by dπ₯ at each of the coordinates zero, zero and two, zero is zero.
00:02:49.600 --> 00:02:50.840
So the line segments at these coordinates are horizontal.
00:02:53.480 --> 00:02:58.120
The value of dπ¦ by dπ₯ at the coordinate two, one is a half.
00:03:00.040 --> 00:03:13.840
Note that the line segment at this point would also pass through the coordinate zero, zero if it were extended, as we travel one unit upwards for every two units across to obtain a point on the line with slope equal to a half.
00:03:16.240 --> 00:03:24.800
The value of dπ¦ by dπ₯ at the coordinate zero, one is negative a half.
00:03:25.880 --> 00:03:32.320
This means that the line segment at this point is a mirror image of the line segment at the coordinate two, one.
00:03:32.720 --> 00:03:37.960
Note that the line segment at zero, one would pass through the coordinate two, zero if extended.
00:03:37.960 --> 00:03:45.960
The value of dπ¦ by dπ₯ at the coordinate two, two is two.
00:03:46.920 --> 00:03:50.600
This means that, for every one unit across, we travel two units upwards.
00:03:51.520 --> 00:03:59.000
And so the line segment at this point would pass through the coordinate one, zero if extended.
00:04:00.040 --> 00:04:06.040
The value of dπ¦ by dπ₯ at the coordinate zero, two is negative two.
00:04:08.120 --> 00:04:11.320
So the line segment at this point is the mirror image of the line segment at the coordinate two, two.
00:04:13.080 --> 00:04:19.760
Note that this line segment would also pass through the coordinate one, zero if extended.
00:04:20.360 --> 00:04:25.240
This completes the sketch of the slope field for the given differential equation at the indicated six points.
00:04:27.360 --> 00:04:32.800
The short line segments in a slope field represent possibilities for tangent lines to solutions of the differential equation.
00:04:33.240 --> 00:04:41.240
This is useful as it allows us to see a visual representation of the curves that could result as solutions of the differential equation.
00:04:41.240 --> 00:04:43.480
Letβs now move on to the second part of the question.
00:04:43.880 --> 00:05:01.400
Part ii) Let π¦ equals π of π₯ be the particular solution to the given differential equation with the initial condition π of three equals four.
00:05:01.600 --> 00:05:09.520
Write an equation of the tangent to the graph of π of π₯ at π₯ equal three.
00:05:10.600 --> 00:05:13.600
Use your equation to approximate π of 3.1.
00:05:13.600 --> 00:05:25.040
In order to write an equation of the tangent to the graph of π of π₯ at π₯ equal three, letβs recall one of the general forms of the equation of a line.
00:05:25.800 --> 00:05:46.720
The equation of a line can be written in the form π¦ equals ππ₯ plus π, where π is the slope or gradient of the line and π is the value of π¦ where the line crosses the π¦-axis.
00:05:47.880 --> 00:05:53.920
We will switch to using the letter π‘ here instead of π¦ so that we do not get mixed up with the variable π¦ given to us in the question.
00:05:55.560 --> 00:06:14.760
In order to calculate the slope of the tangent to the graph of π of π₯ at π₯ equal three, we need to calculate the gradient function of π, or in other words the first derivative of π with respect to π₯ at π₯ equal three.
00:06:15.680 --> 00:06:19.720
We are told that π¦ equals π of π₯ is a solution to the given differential equation.
00:06:20.480 --> 00:06:26.880
So the gradient function of π is just dπ¦ by dπ₯ equals π¦ squared over two π₯ minus two.
00:06:28.720 --> 00:06:32.120
We are also told that π of three equals four.
00:06:33.680 --> 00:06:43.320
Substituting π₯ equals three and π¦ equals four into dπ¦ by dπ₯, we obtain the value four.
00:06:43.720 --> 00:06:45.600
So the slope of the tangent line in question is four.
00:06:47.360 --> 00:06:59.280
Since the point three, four lies on a tangent line, we can substitute π₯ equal three π‘ equals four into the equation π‘ equals four π₯ plus π to find π.
00:07:01.200 --> 00:07:10.400
Doing so, we find that four equals four times three plus π, which implies that π equals four minus 12, which is negative eight.
00:07:10.760 --> 00:07:20.920
So the equation of the tangent to the graph of π of π₯ at π₯ equal three is π‘ equals four π₯ minus eight.
00:07:22.720 --> 00:07:48.520
The next part of the question asks us to approximate the value of the function π at π₯ equal 3.1 using this equation Substituting π₯ equals 3.1 into the equation π‘ equals four π₯ minus eight, we obtain four times 3.1 minus eight, which equals 12.4 minus eight, which equals 4.4.
00:07:50.640 --> 00:07:59.160
So the value of the function π at π₯ equal 3.1 as approximated by the tangent to π at π₯ equal three is 4.4.
00:08:01.280 --> 00:08:03.000
Letβs now answer part iii of the question.
00:08:03.760 --> 00:08:16.800
Part iii) Find the particular solution π¦ equals π of π₯ to the given differential equation with the initial condition π of three equals four.
00:08:18.600 --> 00:08:29.280
We previously rewrote the given differential equation as dπ¦ by dπ₯ equals π¦ squared over two π₯ minus two.
00:08:29.840 --> 00:08:37.080
We are now required to solve this differential equation for the particular solution π¦ equals π of π₯ with the initial condition π of three equals four.
00:08:39.680 --> 00:08:46.280
In order to do this, note that this is a separable differential equation.
00:08:47.160 --> 00:09:00.440
This means that we can separate all of the π¦ and dπ¦ terms to one side of the equation and all the π₯ and dπ₯ terms to the other side of the equation.
00:09:01.640 --> 00:09:10.840
Doing so, we obtain one over π¦ squared dπ¦ equals one over two π₯ minus two dπ₯.
00:09:11.160 --> 00:09:16.840
Separating the variables like so is the first step to solving a first-order separable differential equation.
00:09:18.200 --> 00:09:21.120
The second step is to integrate both sides of the resulting equation.
00:09:23.160 --> 00:09:26.400
We can rewrite one over π¦ squared as π¦ to the power of minus two.
00:09:26.920 --> 00:09:38.920
To integrate π¦ to the power of negative two with respect to π¦, we just increase the exponent by one and divide by the new exponent.
00:09:40.800 --> 00:09:55.560
To integrate one over two π₯ minus two, we take the natural logarithm of the absolute value of two π₯ minus two and divide it by two, as per the formula.
00:09:56.040 --> 00:09:58.560
Remember that the natural logarithm is not defined for negative arguments.
00:09:59.640 --> 00:10:03.720
So the absolute value sign around two π₯ minus two is necessary.
00:10:05.920 --> 00:10:26.360
Remembering the constants of integration, we obtain negative π¦ to the power of negative one plus π one equals a half multiplied by the natural logarithm of the absolute value of two π₯ minus two plus π two, where π one and π two are the constants of integration.
00:10:28.520 --> 00:10:48.200
Collecting the constants of integration together on the right-hand side then multiplying both sides of the equation by π¦ and then dividing both sides of the equation by a half multiplied by the natural logarithm of the absolute value of two π₯ minus two plus π two minus π one.
00:10:49.200 --> 00:11:03.200
We obtain that π¦ equals negative one over a half multiplied by the natural logarithm of the absolute value of two π₯ minus two plus π two minus π one.
00:11:03.480 --> 00:11:12.880
To simplify the expression on the right-hand side, we multiply the numerator and denominator by two.
00:11:17.520 --> 00:11:21.920
We can denote the constant two times π two minus π one with the letter π.
00:11:22.880 --> 00:11:32.560
This completes the third step to solving a first-order separable differential equation, which is to write the general solution in the form π¦ equals π of π₯.
00:11:32.960 --> 00:11:39.680
The solution we have found is called a general solution because it contains the constant π, which is undetermined.
00:11:40.120 --> 00:11:47.360
The fourth and final step to solving a first-order separable differential equation is to use the initial conditions, if given, to find the particular solution.
00:11:49.480 --> 00:11:52.760
A particular solution should not contain any undetermined constants.
00:11:55.320 --> 00:12:07.760
We will use the initial condition π₯ equal three, π¦ equals four, which is given to us in the question, to determine the value of π and therefore find a particular solution to the differential equation given to us in the question.
00:12:08.080 --> 00:12:23.680
Substituting π₯ equal three and π¦ equals four into the general solution, we find that four equals negative two over the natural logarithm of four plus π.
00:12:25.520 --> 00:12:39.640
Multiplying both sides of the equation by the natural logarithm of four plus π then subtracting four times the natural logarithm of four from both sides and then dividing both sides by four.
00:12:40.400 --> 00:12:49.200
We obtain that π is equal to negative a half minus the natural logarithm of four.
00:12:49.640 --> 00:13:04.440
Substituting this value of π into the general solution π¦, we obtain negative two over the natural logarithm of the absolute value of two π₯ minus two minus a half minus the natural logarithm of four.
00:13:06.600 --> 00:13:17.680
This is the particular solution π¦ equals π of π₯ to the given differential equation with the initial condition π of three equals four.
00:13:18.680 --> 00:13:20.360
Letβs rewrite this particular solution in a nicer way.
00:13:22.840 --> 00:13:42.560
Using the fact that the difference of logarithms is equal to the logarithm of the quotient, we can rewrite the natural logarithm of the absolute value of two π₯ minus two minus the natural logarithm of four as the natural logarithm of the absolute value of two π₯ minus two divided by four.
00:13:44.680 --> 00:13:53.200
Next, we multiply the numerator and denominator of the bigger quotient by two and simplify the argument inside the natural logarithm.
00:13:53.840 --> 00:14:05.760
Now using the logarithm power rule, we can move two from the front of the natural logarithm to the exponent of the argument of the logarithm.
00:14:08.760 --> 00:14:15.480
Since squaring an absolute value makes the absolute value sign redundant, we can get rid of the absolute value sign from the argument of the natural logarithm.
00:14:16.800 --> 00:14:36.280
Taking the negative sign, which is outside the whole quotient, inside the denominator, we can rewrite their particular solution as four over one minus the natural logarithm of π₯ minus one all squared divided by four.
00:14:39.200 --> 00:14:42.520
This completes the answer to the third and final part of the question.